ANALISIS LONGSORAN RUAS JALAN CENING KECAMATAN SINGOROJO KABUPATEN KENDAL JAWA TENGAH - Daniel Aprinando Hutahaean; Tri Sumirat Kartiko; Sri Prabandiyani; Bambang Pardoyo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
This Final Project contained about land stability and it countermeasures on roads Cening Sub-district of Singorojo District of Kendal Central Java. This road crosses the hills with unstable soil conditon. Based on the soil drilling test result, it’s contain of clay, clay stone ( splinter ), and clay stone ( clay shale ) layers. This Final Project analyzes value of the slope safety factor that included a condition when occured of the movement of soil slopes which is caused by instability on slopes due to degdradation of soil layers, manual calculation of slope stability using Fellenius method and Plaxis V.8.2 computer program. Based on the to manual calculation of slope stability using Fellenius method,it’s obtained value of the slope safety factor equal to 1,074 and use Plaxis software obtained value of the slope safety factor equal to 1,081. Those values of the slope safety factor are still less than slope stability regulation equal to 1,5, with the result that the slope condition is prone to landslide. The Analysis result indicate that reinforcement slope with bored pile with diameter of 0,55 m in depth of five meters which is placed at the bottom of the slope, it’s the alternative handling had increased the value of the safety factor with the factor of safety of the existing condition which is from 1,081 become 1,812.